First-Pass Effect in Basilar Artery Occlusions: Insights From the Endovascular Treatment of Ischemic Stroke Registry. Issue 12 (December 2021) - Aubertin, Mathilde; Weisenburger-Lile, David; Gory, Benjamin; Richard, Sébastien; Blanc, Raphael; Ducroux, Célina; Piotin, Michel; Labreuche, Julien; Lucas, Ludovic; Dargazanli, Cyril; Benali, Amel; Bourcier, Romain; et al.
Abstract : Background and Purpose: In the settings of thrombectomy, the first-pass effect (FPE), defined by a complete recanalization after one pass with no rescue therapy, has been shown to be associated with an improved outcome. As this phenomenon has been predominantly described in anterior circulation strokes, we aimed to study the prevalence, outcomes, and predictors of FPE in patients with a basilar artery occlusion. Methods: From a prospective multicentric registry, we collected the data of all consecutive basilar artery occlusion patients who underwent thrombectomy and compared the outcomes of patients who achieved FPE and those who did not. We also compared FPE patients with those who achieved a complete recanalization with >1 pass. Finally, a multivariate analysis was performed to determine the predictors of FPE. Results: Data from 280 patients were analyzed in our study, including 84 of 280 patients (30%) with an atheromatous etiology. An FPE was achieved in 93 patients (33.2%), with a significantly higher proportion of good outcomes (modified Rankin Scale score 0-2 at 3 months) and lower mortality than non-FPE patients. An FPE was also associated with improved outcomes compared with patients who went on to have full recanalization with >1 pass. Contact aspiration as first-line strategy was a strong predictor of FPE, whereas baseline antiplatelets and atheromatous etiology were negative predictors. Conclusions: In our study, an FPE was achieved in approximately one-third of patients with a basilar artery occlusion and was associated with improved outcomes. More research is needed to improve devices and techniques to increase the incidence of FPE. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03776877. Abstract : Supplemental Digital Content is available in the text.